2000
DOI: 10.1093/alcalc/35.2.176
|View full text |Cite
|
Sign up to set email alerts
|

United Kingdom Multicentre Acamprosate Study (Ukmas): A 6-Month Prospective Study of Acamprosate Versus Placebo in Preventing Relapse After Withdrawal From Alcohol

Abstract: A 6-month randomized controlled study of acamprosate versus placebo in preventing relapse following withdrawal from alcohol was undertaken in 20 centres throughout the UK. Patients diagnosed as alcohol-dependent and detoxified within the preceding 5 weeks were randomly assigned to treatment with either acamprosate (A) 666 mg three times/day or identical placebo (P). A total of 664 patients were screened; 581 were entered into the treatment phase. One-third were episodic drinkers, 84% were male, 44% were unmarr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
122
3
4

Year Published

2003
2003
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 196 publications
(133 citation statements)
references
References 36 publications
4
122
3
4
Order By: Relevance
“…Thus, screening for alcohol-related problems among trauma patients, as well as intervention (from brief counselling to referral for alcoholdependence treatment) is of relevance, although in practice this is poorly enforced (NHTSA, 2000;Runge, 2000). It is well known that there is a marked drop-out rate among alcohol-dependent patients during treatment (Noone and Watt, 2000;Chick et al, 2000). This is reflected in our study, the initial number of patients included was 176 and after the 12 months of treatment, more than half (107) had dropped out, with only 69 patients remaining in the study.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, screening for alcohol-related problems among trauma patients, as well as intervention (from brief counselling to referral for alcoholdependence treatment) is of relevance, although in practice this is poorly enforced (NHTSA, 2000;Runge, 2000). It is well known that there is a marked drop-out rate among alcohol-dependent patients during treatment (Noone and Watt, 2000;Chick et al, 2000). This is reflected in our study, the initial number of patients included was 176 and after the 12 months of treatment, more than half (107) had dropped out, with only 69 patients remaining in the study.…”
Section: Discussionmentioning
confidence: 99%
“…However, naltrexone's maintenance of abstinence in alcoholdependent patients was not remarkable in one study (Guardia et al 2002) and was absent in another (Krystal et al 2001). Chick et al (2000) provided disappointing effectiveness of acamprosate in their investigation. It is important to note that continuous use of opiate antagonists induces a rebound increase in central opiate receptors (Cowen et al 1999;Overstreet et al 1999;Parkes and Sinclair 2000).…”
Section: Future Directionsmentioning
confidence: 97%
“…Opiate antagonists (HeinĂ€lĂ€ et al 2001;Litten and Allen 1998;O'Malley et al 1992;Monti et al 2001;Rubio et al 2001;Volpicelli et al 1992), acamprosate (Ansoms et al 2000;Besson et al 1998;Chick et al 2000;Lesch et al 2001;Rubio et al 2001;Sass et al 1996;Tempesta et al 2000;Litten and Allen 1998; see overview by Mason 2001) or a combination of these drugs (Kranzler and Van Kirk 2001) are currently prescribed to reduce alcohol consumption in alcoholics. In preclinical studies, opiate antagonists are capable of minimizing acute drinking of alcohol (Altshuler et al 1980;Badia-Elder et al 1999;Froehlich et al 1990;Heyser et al 2003;Hölter and Spanagel 1999;Hyytia and Sinclair 1993;Overstreet et al 1999;Samson and Doyle 1985), as well as reducing alcohol seeking by an alcohol conditioned stimulus (Liu and Weiss 2002a;Koob et al 2003).…”
Section: Future Directionsmentioning
confidence: 99%
“…Pharmacovigilance data [23] in 1.5 million patients indicated no serious adverse events, and a Cochrane review [6] found the most common side effects (significantly different to placebo) to be gastro-intestinal symptoms (see Table 1) especially diarrhoea (effect size 0.11[0.09-0.13]) . If diarrhoea is severe, temporary dose reduction was beneficial [22,24]. More recent studies not included in earlier meta-analyses [25,26] confirm these earlier findings, diarrhoea being reported significantly more frequently in the acamprosate group, 1998mg/d (p=.004), and nervousness/ anxiety in the placebo group (p=.002) [26].…”
Section: Pharmacokinetic Considerations and Implications For Safetymentioning
confidence: 67%
“…there are reports from two studies of three patients taking intentional overdoses of 8-120 tablets with no 'untoward symptoms' [19,22].…”
Section: Pharmacokinetic Considerations and Implications For Safetymentioning
confidence: 99%